First treatments for Lattice stereotactic body radiation therapy using magnetic resonance image guided radiation therapy. (March 2023) - Price, Alex T.; Schiff, Joshua P.; Zhu, Tong; Mazur, Thomas; Kavanaugh, James A.; Maraghechi, Borna; Green, Olga; Kim, Hyun; Spraker, Matthew B.; Henke, Lauren E.
Highlights: Lattice SBRT for mobile abdominal lesion can be treated with MRgRT. The use of MRgRT Lattice SBRT limits the need for full ITV treating and invasive fiducial placement. Interfractional MRgRT imaging demonstrated increased signal intensity in the area of high dose treatment. Abstract: Two abdominal patients were treated with Lattice stereotactic body radiation therapy (SBRT) using magnetic resonance guided radiation therapy (MRgRT). This is one of the first reported treatments of Lattice SBRT with the use of MRgRT. A description of the treatment approach and planning considerations were incorporated into this report. MRgRT Lattice SBRT delivered similar planning quality metrics to established dosimetric parameters for Lattice SBRT. Increased signal intensity were seen in the MRI treatments for one of the patients during the course of treatment.